Effects of stocking density and season on growth performance and welfare of broiler chickens in Ibadan, Nigeria (2017)
The study was carried out to investigate the effects of season and stocking density on the growth performance and welfare of broiler chickens in Ibadan, Nigeria. In a seven-week feeding trial, a total of 96 one-week old Arbor Acre broiler chickens were randomly distributed to three stocking densities (birds/m2) of 10, 12, and 14 at the rate of 32 birds per stocking density (SD) during each season; Late Wet (LWS) and Late Dry (LDS). Total Feed Intake (TFI, g), Final Live Weight (FLW, g), Feed Conversion Rate (FCR), Live weight/m2(LW/m2), Normal Gait Score(NGS,%), Survival Rate(SR %), Heterophil: Lymphocyte(H:L) ratio, were assessed. Data were subjected to statistics analysis (ANOVA at α0.05). Birds raised during LWS had higher TFI (4756.60) than LDS birds, while SD had no effect on TFI. Birds on SD of 14 birds/m2 had lower FLW. The FCR was lower during LDS and on SD 10 and 12 Birds/m2. The LW/m2 was higher in birds on SD 14birds/m2. The LWS had higher NGS and lower H:L ratio. Season and SD had no effect on SR. The NGS and H:L were not affected by SD. Broiler chickens could be raised at stocking density of 14birds/m2 during either of the seasons.